Effect of Electrochemical Treatment on Electrical Conductivity of Conical Carbon Nanotubes - S. M. Khantimerov; P. N. Togulev; E. F. Kukovitsky; N. M. Lyadov; N. M. Suleimanov (Journal of Nanotechnology)
Interaction of conical carbon nanotubes (CNTs) with hydrogen during electrochemical treatment and its effect on their electronic properties was studied. The temperature dependencies of electroconductivity of initial and electrochemically hydrogenated conical CNTs were investigated by using four-probe van der Pauw method. The studies revealed that the electrochemical hydrogen absorption leaded to a significant reduction in the electroconductivity of conical carbon nanotubes. We assume that these changes can be associated with a decrease in the concentration of charge carriers as a result of hydrogen localization on the carbon π-orbitals, the transition from sp2 to sp3 hybridization of conical CNTs band structure, and, therefore, a metal-semiconductor-insulator transition.